Ответ(ы) на вопрос:
[latex] \sqrt{x^2-6x+9}= \sqrt{(x-3)^2} =|x-3|=0.4 , x=2.6 \\ \frac{6- \sqrt{6} }{ \sqrt{18}- \sqrt{3} }= \frac{ \sqrt{6}( \sqrt{6}-1) }{ \sqrt{3}( \sqrt{6}-1) } = \frac{ \sqrt{6} }{ \sqrt{3} }= \sqrt{ \frac{6}{3} } = \sqrt{2} \\ \frac{16-x}{4+ \sqrt{x} } = \frac{(4- \sqrt{x} )(4+ \sqrt{x} )}{4+ \sqrt{x} }=4- \sqrt{x} [/latex]
Тогда я прикрепляю скриншот в виде картинки
=√(х-3)²=|x-3|=|2,6-3|=|-0,6|=0,6(√6)²-√6 √6(√6-1) √6=_______=_______=______=√6/3=√2√6*√3-√3 √3(√6-1) √3 4²- (√x)² (4-√x)(4+√x)=__________=______________=4-√x 4+√x 4+√x
Не нашли ответ?
Похожие вопросы